2018
DOI: 10.31101/jhes.605
|View full text |Cite
|
Sign up to set email alerts
|

Martabat pasien paliatif di rumah sakit pkumuhammadiyah gamping

Abstract: Penelitian ini bertujuan untuk mengetahui martabat pasien paliatif di RS PKU Muhammadiyah Gamping. Penelitian ini dilakukan di RS PKU Muhammadiyah Gamping dengan metode deskriptif survey. Seratus pasien paliatif ditemukan dalam satu bulan dan mengisi kuesioner patient dignity inventory yang telah diterjemahkan ke Bahasa Indonesia. Hasil penelitian ini ditemukan sebagian besar pasien paliatif memiliki martabat utuh, namun terdapat pasien yang memiliki martabat retak pada gejala yang membuat tertekan secara fisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Research by Nur Hasanah and Arianti (2018) [6] on palliative patients showed that the majority of patients had a good intact dignity, but some patients had fractured or disturbed dignity. Complete dignity is when there are no problems that occur with the patient's dignity, while patients who have a fractured dignity experience symptoms that make physical distress (pain, difficult breathing, and nausea).…”
Section: Introductionmentioning
confidence: 99%
“…Research by Nur Hasanah and Arianti (2018) [6] on palliative patients showed that the majority of patients had a good intact dignity, but some patients had fractured or disturbed dignity. Complete dignity is when there are no problems that occur with the patient's dignity, while patients who have a fractured dignity experience symptoms that make physical distress (pain, difficult breathing, and nausea).…”
Section: Introductionmentioning
confidence: 99%